Are abstract action words embodied? An fMRI investigation at the interface between language and motor cognition - Sakreida, Katrin; Scorolli, Claudia; Menz, Mareike M.; Heim, Stefan; Borghi, Anna M.; Binkofski, Ferdinand (Frontiers in Human Neuroscience, 2013)
The cognitive and neural representation of abstract words is still an open question for theories of embodied cognition. Generally, it is proposed that abstract words are grounded in the activation of sensorimotor or at least experiential properties, exactly as concrete words. Further behavioral theories propose multiple representations evoked by abstract and concrete words. We conducted a functional magnetic resonance imaging study to investigate the neural correlates of concrete and abstract multi-word expressions in an action context. Participants were required to read simple sentences which combined each concrete noun with an adequate concrete verb and an adequate abstract verb, as well as an adequate abstract noun with either kind of verbs previously used. Thus, our experimental design included a continuum from pure concreteness to mere abstractness. As expected, comprehension of both concrete and abstract language content activated the core areas of the sensorimotor neural network namely the left lateral (precentral gyrus) and medial (supplementary motor area) premotor cortex. While the purely concrete multi-word expressions elicited activations within the left inferior frontal gyrus (pars triangularis) and two foci within the left inferior parietal cortex, the purely abstract multi-word expressions were represented in the anterior part of left middle temporal gyrus that is part of the language processing system. Although the sensorimotor neural network is engaged in both concrete and abstract language contents, the present findings show that concrete multi-word processing relies more on the sensorimotor system, and abstract multi-word processing relies more on the linguistic system.